Multi-class Text Classification using Support Vector Machines (SVMs) - Nguyen, Hoang Nghia (2019)
My project presents the experiment conclusion of the suited of Support vector machines for multi-class text in different datasets and discusses the process of text classification with a series of novel Multi-class Support vector machines methods. It address the following points: • How to represent text documents as feature vectors and the effect of text representation on classification result? • How to use the binary classifiers for Multi-classification problem? And the empirical experiment on different dataset both in English and Vietnamese